Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO308/1 - Eric Pieter Achterberg; Mia Schumacher (PANGAEA, 2025)
Raw water column data were collected aboard RV SONNE during cruise SO308 (GEOTRACES SIO) using a 12kHz Kongsberg EM 122 multibeam echosounder with 2x2 beam width. The expedition took place during 2024-10-31 – 2024-12-22 from Durban (South Africa) to Fremantle (Australia) in the South Indian Ocean. The main scientific aim of the cruise was to establish the distributions of trace elements and their isotopes (TEIs), quantify their sources from the four major ocean boundaries (rivers, atmosphere, exchange with sediments, ocean crust), and determine their biogeochemical cycling and relationships to large scale ocean circulation along a cruise track in the South Indian Ocean. Data were recorded in the EEZs of Mozambique, Europa Island (France), Bassas da India (France) and outside EEZs. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by GEOMAR Helmholtz Centre for Ocean Research, provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.